ChemInform Abstract: Fe3O4‐Nanoparticles Catalyzed an Efficient Synthesis of Nitriles from Aldehydes. Issue 46 (27th October 2016) - Ghosh, Pranab; Saha, Bittu; Pariyar, Gyan Chandra; Tamang, Abiral; Subba, Raju
Abstract: The reaction tolerates a diverse range of functionalized aryl aldehydes and is applicable to alkenyl as well as alkyl aldehydes.